2012
DOI: 10.1136/postgradmedj-2012-131005
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among patients with symptomatic carotid disease

Abstract: Patients with symptomatic carotid disease had poorer HRQoL, especially its mental components, than the general population. The severity of the disease was significantly associated only with the SF-36 role-physical subscale. HRQoL in patients with symptomatic carotid disease was poorer in women than in men, and was not affected by age and other demographic and clinical characteristics of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
10
2
1
Order By: Relevance
“…The difference may be explained by differences in patient groups, as patients in the SAPPHIRE trial had greater burden of comorbidity. In another smaller single centre study, SF-36 scores for physical functioning, role-physical, bodily pain, general health, vitality were higher than in our study, but role-emotional and mental health scores were lower (Vlajinac et al, 2013). One of the reasons for these differences might be the difference in disease severity of subjects and the number of included patients in the study.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The difference may be explained by differences in patient groups, as patients in the SAPPHIRE trial had greater burden of comorbidity. In another smaller single centre study, SF-36 scores for physical functioning, role-physical, bodily pain, general health, vitality were higher than in our study, but role-emotional and mental health scores were lower (Vlajinac et al, 2013). One of the reasons for these differences might be the difference in disease severity of subjects and the number of included patients in the study.…”
Section: Discussioncontrasting
confidence: 87%
“…Although there were no statistically significant difference in mean SF-36v2 score for women and men in our study, a slight difference has been observed in other studies (Sturm, 2004;Almborg, 2009) and in general populations (Hopman et al, 2004;Vlajinac et al, 2013). This might be because women experience more mental impairment, depression and fatigue after stroke, which is related to HRQoL (Naess et al, 2006).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A British study [21] with 13% asymptomatic patients (equal to the AtheroExpress cohort) reports RE that is 30 points higher than AtheroExpress patients while RP is 20 points lower. The Serbian cohort of Vlajinac et al [22] with 35% stroke patients reported an excellent PF (71.7) at baseline but the same pattern exists within the role limitation subdomains: lower PF and higher RE than Athero-Express patients (−15 and +15 points respectively). All cohorts, including the AtheroExpress cohort, have a mean age of around 70.…”
Section: Discussionmentioning
confidence: 62%
“…Развитию послеоперацион-ной когнитивной дисфункции у больных после КШ могут способствовать и бессимптомные стенозы каро-тидных артерий [13]. Также в последнее время было показано, что у больных со стенозами каротидных арте-рий КЖ было ниже, чем в общей популяции, что отме-чено по шкалам физического состояния (RP), социаль-ного функционирования (SF), эмоционального состоя-ния (RE) и самооценке психического здоровья (MH) опросника SF-36 [14].…”
Section: таблица 3 интегральные показатели качества жизниunclassified